Existence of SARS-CoV-2 RNA on ambient particulate matter samples: A nationwide study in Turkey - Kayalar, Ozgecan; Ari, Akif; Babuccu, Gizem; Konyalilar, Nur; Dogan, Ozlem; Can, Fusun; Sahin, Ulku A.; Gaga, Eftade O.; Kuzu, S. Levent; Ari, Pelin Erturk; Odabasi, Mustafa; Tasdemir, Yucel; et al. (ELSEVIER, 2021)
Coronavirus disease 2019 (COVID-19) is caused by the SARS-CoV-2 virus and has been affecting the world since the end of 2019. The disease led to significant mortality and morbidity in Turkey, since the first case was reported on March 11th, 2020. Studies suggest a positive association between air pollution and SARS-CoV-2 infection. The aim of the present study was to investigate the role of ambient particulate matters (PM), as potential carriers for SARS-CoV-2. Ambient PM samples in various size ranges were collected from 13 sites including urban and urban-background locations and hospital gardens in 10 cities across Turkey between 13th of May and 14th of June 2020 to investigate the possible presence of SARS-CoV-2 RNA on ambient PM. A total of 203 daily samples (TSP, n = 80; PM2.5, n = 33; PM2.5-10, n = 23: PM10 mu m, n = 19; and 6 size segregated PM, n = 48) were collected using various samplers. The N1 gene and RdRP gene expressions were analyzed for the presence of SARS-CoV-2, as suggested by the Centers for Disease Control and Prevention (CDC). According to real time (RT)-PCR and three-dimensional (3D) digital (d) PCR analysis, dual RdRP and NI gene positivity were detected in 20 (9.8%) samples. Ambient PM-bound SARS-CoV-2 was analyzed quantitatively and the air concentrations of the virus ranged from 0.1 copies/m(3) to 23 copies/m(3). The highest percentages of virus detection on PM samples were from hospital gardens in Tekirdag, Zonguldak, and Istanbul, especially in PM2.5 mode. Findings of this study have suggested that SARS-CoV-2 may be transported by ambient partides, especially at sites close to the infection hot-spots. However. whether this has an impact on the spread of the virus infection remains to be determined. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: SARS-CoV-2; Particulate matter; Airborne; 3D-dPCR; INFLUENZA-VIRUS; COVID-19; POLLUTANTS; URBAN; PM2.5; Environmental Sciences & Ecology